2017
DOI: 10.1111/ejn.13765
|View full text |Cite
|
Sign up to set email alerts
|

Absolute auditory threshold: testing the absolute

Abstract: The mechanisms underlying the detection of sounds in quiet, one of the simplest tasks for auditory systems, are debated. Several models proposed to explain the threshold for sounds in quiet and its dependence on sound parameters include a minimum sound intensity ('hard threshold'), below which sound has no effect on the ear. Also, many models are based on the assumption that threshold is mediated by integration of a neural response proportional to sound intensity. Here, we test these ideas. Using an adaptive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
3
5
0
Order By: Relevance
“…The spontaneous rate of the model is below 1/s. This agrees with the parameter values reported in [ 25 ] (i.e., λ 1 = 1.59/s and λ 1 = 0.58/s in their Fig 11) and in [ 32 ] (i.e., λ 1 = 0.09/s in their Fig 3 ). The attenuation is considerably higher than those for the classical audio-frequency range (after converting the gain factor using Eq (1) ), but this was expected for the considered frequencies (8 Hz and 16 Hz), because the thresholds for these frequencies are considerably higher than for the frequencies that were considered in the literature for the fitting of the model.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The spontaneous rate of the model is below 1/s. This agrees with the parameter values reported in [ 25 ] (i.e., λ 1 = 1.59/s and λ 1 = 0.58/s in their Fig 11) and in [ 32 ] (i.e., λ 1 = 0.09/s in their Fig 3 ). The attenuation is considerably higher than those for the classical audio-frequency range (after converting the gain factor using Eq (1) ), but this was expected for the considered frequencies (8 Hz and 16 Hz), because the thresholds for these frequencies are considerably higher than for the frequencies that were considered in the literature for the fitting of the model.…”
Section: Discussionsupporting
confidence: 92%
“…A similar processing mechanism is supported also by the results of the modelling. The exponent of the model used to account for the infrasound data of the present study is close to 3, the integer exponent found to describe well a variety of temporal-integration data (e.g., [25,32,41]), spectral-and spectrotemporal integration data [42], and binaural integration data [46] for stimuli in the classical audio-frequency range. The spontaneous rate of the model is below 1/s.…”
Section: Multiple Burstssupporting
confidence: 64%
See 1 more Smart Citation
“…It is unclear, however, whether a hard threshold exists in the auditory system. Heil and Matysiak 23 performed experiments specifically designed to address the question of whether there is a hard threshold at the perceptual level but found no evidence for the existence of such a threshold (see also 24 ). In fact, detection thresholds for tones presented in quiet, and the dependence of threshold on tone duration and envelope, can be well understood without a hard threshold (e.g., 23,25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Heil and Matysiak 23 performed experiments specifically designed to address the question of whether there is a hard threshold at the perceptual level but found no evidence for the existence of such a threshold (see also 24 ). In fact, detection thresholds for tones presented in quiet, and the dependence of threshold on tone duration and envelope, can be well understood without a hard threshold (e.g., 23,25 ). Ward et al 22 argue that SR might also be observed in the case of a "soft threshold", i.e., a non-linear transfer function between instantaneous input and output, such as an exponential or logistic function, if sufficiently steep.…”
Section: Discussionmentioning
confidence: 99%